2021
DOI: 10.3390/biomedicines9060697
|View full text |Cite
|
Sign up to set email alerts
|

Syndecan-1 Expression Is Increased in the Aortic Wall of Patients with Type 2 Diabetes but Is Unrelated to Elevated Fasting Plasma Glucagon-Like Peptide-1

Abstract: A reduced prevalence of a thoracic aortic aneurysm (thoracic AA) is observed in type 2 diabetes (T2D). Glucagon-like peptide-1 (GLP-1)/GLP-1-based anti-diabetic therapy has indicated protective effects in thoracic AA and regulates the processes controlling the vascular tissue expression of Syndecan-1 (Sdc-1). Sdc-1 expression on macrophages infiltrating the aortic tissue contributes to a counter-regulatory response to thoracic AA formation in animal models through the interplay with inflammation/proteolytic ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(9 citation statements)
references
References 54 publications
(69 reference statements)
1
7
0
Order By: Relevance
“…In the current study, we report for the first time, by ELISA and histological analysis, that Sdc-1 is one of the members of the PGs overexpressed in human TAA aorta medial layer. Our immunofluorescence analysis showed that Sdc-1 expression is increased not only in media layer, but also in the intima and adventitia layers, in agreement with Ntika et al (30).…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…In the current study, we report for the first time, by ELISA and histological analysis, that Sdc-1 is one of the members of the PGs overexpressed in human TAA aorta medial layer. Our immunofluorescence analysis showed that Sdc-1 expression is increased not only in media layer, but also in the intima and adventitia layers, in agreement with Ntika et al (30).…”
Section: Discussionsupporting
confidence: 93%
“…RNA level of Sdc-1 (referred previously as syndecan) was previously reported to be increased after vascular injury (29). More recently , an increase of Sdc-1 protein level was observed in the adventitia of human aortas with ascending TAA (30).…”
Section: Discussionmentioning
confidence: 92%
“…Syndecan-1 is a key constituent of glycocalyx on most endothelial cells in the body, and its soluble form is generated by shedding from the endothelial glycocalyx indicative of damage to endothelial cells ( 45 ). As suggested by a previous study ( 18 ), it is possible that increased local shedding of syndecan-1 from the aneurysm is masked by the total pool of the biomarker, resulting in non-significant associations with AA in this study. Furthermore, since we only measured syndecan-1 in plasma and not aortic tissue, this may altogether explain why we do not reproduce the previously found association.…”
Section: Discussionmentioning
confidence: 66%
“…A previous study reported concentrations of syndecan-1, a key constituent of the endothelial glycocalyx and a regulator of inflammation, to be elevated in aortic tissue, though not in plasma, from patients with ascending AA compared to matched controls ( 18 ). Additionally, a study reported elevated syndecan-1 in PLWH compared to uninfected controls ( 23 ).…”
Section: Discussionmentioning
confidence: 99%
“…The mRNA expression level of SDC-1 (referred previously as syndecan) was previously reported to be increased after vascular injury ( 30 ). More recently, an increase of SDC-1 protein expression was observed in the adventitia of human aortas with ascending TAA ( 31 ).…”
Section: Discussionmentioning
confidence: 95%